Cytokeratin expression in pili annulati hair follicles. - Giehl, K; Dean, D; Dawber, R; Leigh, I; de Berker, D; Wojnarowska, F (2005)
Pili annulati is a rare autosomal inherited hair shaft abnormality of unknown pathogenesis in which clinical examination reveals alternating light and dark bands leading to a shiny appearance of the hair due to cavities within the cortex of the hair shaft. This is the first investigation of the proposed cytokeratin defect in pili annulati hair follicles. Four cryopreserved pili annulati and four control scalp specimens were analysed using immunohistochemistry for different 'hard' trichocytic and 'soft' epithelial cytokeratins including K1, K6, K10, K14, K16, K17, K18, K19, Ha1 and Hb1. There was no difference in staining intensity and quality of staining pattern seen in pili annulati and control scalp specimens. These results suggest that pili annulati is not caused by a defect of the cytokeratins investigated in this study.